Study of fingerprint pattern among medical students in a tertiary hospital in Nepal: a descriptive cross-sectional study - Yadav, Salmalee (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: The fingerprints are most reliable form of identification because they do not change from birth to death. Fingerprints have different variations in their patterns and have great importance in scientific, morphological, criminological, biological and anthropological studies. We studied the fingerprint patterns among the medical students and difference of fingerprint pattern in male and female students.Method: A descriptive cross-sectional study was conducted among 250 medical students of Maharajgunj Medical College. The study was carried from 1st August 2019 to 1st August 2020 after receiving ethical approval from the ethical committee. The fingerprint patterns of both hands were collected and iden-tified with magnifying glass and loops, whorls, arches and composite are documented and analyzed in SPSS 16 version.Result: The most predominant pattern was loop 1092(43.68%) followed by whorls 1035(41.40%), arches 225(9%) and composite 148(5.92%). The males had higher incidence of loops 599(47.9%) compared to females 493(39.40%).Conclusion: Loop fingerprint was predominant pattern in most of the fingers. The loops fingerprint pattern was found to be more prevalent in males than that of females